2019
DOI: 10.1002/cncr.32167
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution on computed tomography imaging and prostate cancer risk and mortality in the AGES‐Reykjavik study

Abstract: Background The World Cancer Research Fund classifies as “strong evidence” the link between obesity and the risk of advanced prostate cancer. In light of the different hormonal profiles associated with where adipose is stored, this study investigated the role of objectively measured body fat distribution and the risk of clinically relevant prostate cancer. Methods This was a prospective study of 1832 men in the Age, Gene/Environment Susceptibility–Reykjavik study. From 2002 to 2006, participants underwent basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 37 publications
2
41
0
Order By: Relevance
“…This study prospectively evaluated adipose tissue distribution using CT scans and found that BMI and WC were associated with increased risk of both advanced and fatal disease. Visceral adiposity was associated with a higher risk of advanced prostate cancer, while higher amounts of thigh subcutaneous fat was associated with increased risk of fatal prostate cancer 11 . Our results, along with these mixed findings from other studies, suggest that more research incorporating accurate measures of adipose tissue distribution is needed to better understand the link between obesity and prostate cancer outcomes.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…This study prospectively evaluated adipose tissue distribution using CT scans and found that BMI and WC were associated with increased risk of both advanced and fatal disease. Visceral adiposity was associated with a higher risk of advanced prostate cancer, while higher amounts of thigh subcutaneous fat was associated with increased risk of fatal prostate cancer 11 . Our results, along with these mixed findings from other studies, suggest that more research incorporating accurate measures of adipose tissue distribution is needed to better understand the link between obesity and prostate cancer outcomes.…”
Section: Discussionmentioning
confidence: 43%
“…Visceral fat area (VFA), subcutaneous fat area (SFA), and PPAT area were measured using radiotherapy planning computed tomography (CT) scans, as previously described 9 . Briefly, VFA and SFA were calculated using a single CT slice at the level of the L4/L5 vertebrae, a validated method used by other groups 11‐13 . PPAT area was calculated using a single CT slice at the first anterior point of the pubic symphysis, as we and others have done previously 9,14,15 .…”
Section: Methodsmentioning
confidence: 99%
“…The findings from Dickerman et al's research, in addition to existing evidence on obesity and prostate cancer, highlight the need to examine lifestyle interventions that target fat loss in promoting optimal prostate cancer outcomes. Two lifestyle behaviors frequently examined within weight‐loss research are diet and exercise.…”
mentioning
confidence: 99%
“…In light of the findings by Dickerman et al and the existing body of knowledge on diet and exercise, new opportunities arise for knowledge development and practice for researchers and clinicians. First, researchers could benefit from including measures that assess visceral fat as outcomes in interventions, whereas clinicians would benefit from collecting knowledge of fat location in addition to the total weight.…”
mentioning
confidence: 99%
See 1 more Smart Citation